Proses Perubahan Morfofonemik Bahasa Makassar - Alnur Suriyanti Hafid; Sri Suryana Dinar (Cakrawala Listra: Jurnal Kajian Sastra, Bahasa, dan Budaya Indonesia, 2018)
This study aims to determine the change process Morphophonemic Makassar language. This study included in the research field and using qualitative descriptive method using generative techniques. Data collection method used is the method see, while the data collecting techniques are observation, recording, and record. Sources of data in this research is the source of written data obtained from Makassar dictionary. And the source of the data obtained from informants spoken native speakers Makassar. From the analysis of the data shows that the change process Morphophonemic the native language there are many changes of phonemes, while the process of changing the phonemes that occur in the native language is prefix a(K)-, prefix a(N)-, the prefix ta(K)-, the prefix pa( K)- and prefix pa(N)-. Keywords: Morphophonemic, process, phoneme changes, and prefix.